Pengaruh Persentasi Perekat Briket Berbahan Dasar Tempurung Kelapa terhadap Nilai Kalor dan Laju Pembakaran - Sukarti, Sukarti; Pangga, Dwi; Ahzan, Sukainil (Jurnal Ilmiah IKIP Mataram, 2023)
The purpose of this study was to determine the effect of adhesive presentation of shell-based briquettes. The material used in the manufacture of briquettes is coconut shell with a variation of the presentation of tapioca starch as an adhesive. This research is an experimental research conducted in three stages, namely material preparation, briquette making, and briquette testing. The variation of the adhesive used is tapioca flour. The results of the briquettes test showed that the higher the adhesive presentation, the higher the calorific value of the briquettes and the higher the adhesive presentation, the lower the burning rate of the briquettes.